An Investigation into Species Reporting by the Top 250 Fortune Global Companies - Drae BENT; Elisabete VIEIRA; Mara MADALENO (PT. Keberlanjutan Strategis Indonesia, 2024)
Purpose:This research paper aims to explore corporate reports published by companies to investigate the extent of species disclosure by top Fortune Global companies.Methodology:This paper uses content analysis to explore and investigate species disclosures in sustainability reports (and equivalents) for the 2020 reporting year, the COVID-19 pandemic era, by the top 250 Fortune Global companies.Findings:The results of this investigation are supported by frequency charts and tables, along with graphical depictions of the data. Our results reveal that species reporting still needs to be expanded to top companies across regions and sectors. Corporate reports are filled with a preference for highly charismatic and widespread species, which aligns with impression management theory. Our results also reveal a positive correlation between companies from high biodiversity risk sectors and the extent of species published in reports. This paper is the first to quantify and assess species reporting by leading Fortune Global companies.Implication:These findings contribute to the discussion on biodiversity reporting practices, particularly in the era of the COVID-19 pandemic, and the importance of working together to prevent species extinction. The results are helpful for policymakers, academic researchers, and all stakeholders who seek to promote and prevent species extinction in organizations.